Hepatitis B knowledge among key stakeholders in Haimen City, China: Implications for addressing chronic HBV infection. Issue 1 (December 2016) - Cohen, Chari; Evans, Alison; Huang, Peixin; London, W.; Block, Joan; Chen, Gang
Abstract Background This article describes hepatitis B-related knowledge, attitudes and practices after completion of the Gateway to Care campaign, a citywide public health education program that targeted city residents, health care providers and individuals chronically infected with hepatitis B virus in Haimen City, China. Methods Pre/post questionnaires assessed hepatitis B knowledge change among health care providers and post-campaign surveys evaluated hepatitis B knowledge, attitudes and behaviors (including stigma-related beliefs and practices) among health care providers, city residents and chronically infected individuals. Focus groups were conducted to gain a more in-depth understanding of the needs of the target communities, and to identify future intervention strategies to improve hepatitis B testing and linkage to care and treatment. Results Results indicate high levels of hepatitis B knowledge among multiple stakeholders in Haimen City, with significant knowledge improvement among health care providers. Stigma-related beliefs and myths regarding separation of infected individuals from certain aspects of family life were common among all stakeholder groups, despite high levels of accurate knowledge about hepatitis B transmission and prevention. Self-report of hepatitis B screening was low among city residents, as was awareness of hepatitis B treatment. Conclusions More efforts are needed to improve awareness of HBV treatment, decrease HBV-related stigma, improve screening rates, and reduce cost of antiviral treatment. Future interventions in Haimen City should be driven by behavioral change theory, to not only improve knowledge, but to improve screening behaviors and address hepatitis B-related stigma and discrimination.